A Hybrid Forecasting Model for Nonstationary and Nonlinear Time Series in the Stochastic Process of CO2 Emission Trading Price Fluctuation. (4th August 2020) - Chai, Shanglei; Du, Mo; Chen, Xi; Chu, Wenjun
Abstract : Predicting CO2 emission prices is an important and challenging task for policy makers and market participants, as carbon prices follow a stochastic process of complex time series with nonstationary and nonlinear characteristics. Existing literature has focused on highly precise point forecasting, but it cannot correctly solve the uncertainties related to carbon price datasets in most cases. This study aims to develop a hybrid forecasting model to estimate in advance the maximum or minimum loss in the stochastic process of CO2 emission trading price fluctuation. This model can granulate raw data into fuzzy-information granular components with minimum (Low), average ( R ), and maximum (Up) values as changing space-description parameters. Furthermore, it can forecast carbon prices' changing space with Low, R, and Up as inputs to support a vector regression. This method's feasibility and effectiveness is examined using empirical experiments on European Union allowances' spot and futures prices under the European Union's Emissions Trading Scheme. The proposed FIG-SVM model exhibits fewer errors and superior performance than ARIMA, ARFIMA, and Markov-switching methods. This study provides several important implications for investors and risk managers involved in trading carbon financial products.